Analisis Pembangunan Infrastruktur Jalan terhadap Pertumbuhan Ekonomi UMKM di Bukit Gado-Gado Kota Padang - Riandy Mardhika Adif; Rifki Hendri; Almizan (SAFE-Network, 2021)
This study aims to determine the analysis of road infrastructure development (X) on the economic growth of MSMEs (Y) in Gado-Gado hill. Infrastructure is the answer to the needs of countries that want to boost economic growth, by helping reduce poverty, improve the quality of life, support the growth of economic centers and increase the mobility of goods and services. Research is a field (Field Research), namely research that takes data directly to the field, this research uses a quantitative approach. The sampling technique was purposive sampling and the number of samples in this study was 51 SMEs. This study uses the Simple Linear Regression model as an analytical tool using the SPSS 21 tool. The results of this study indicate that road Infrastructure Development (X) has a positive and significant effect on MSME economic growth with a tcount value of 6.963> from ttable 1.676 and a significant value resulting in a value of 0.000 <0.05.